2019
DOI: 10.2147/ijn.s224160
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhancement of Radiosensitization by Silver Nanoparticles Functionalized with Polyethylene Glycol and Aptamer As1411 for Glioma Irradiation Therapy</p>

Abstract: BackgroundThe efficacy of radiotherapy for glioma is often limited by the radioresistance of glioma cells. The radiosensitizing effects of silver nanoparticles (AgNPs) on glioma were found in the previous studies of our group. In order to enhance the radiosensitivity of tumor cells and selectively kill them while reducing the side effects of irradiation therapy, targeted modification of AgNPs is urgently needed.Materials and methodsIn the present study, AgNPs functionalized with polyethylene glycol (PEG) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 49 publications
1
68
0
Order By: Relevance
“…With the nanotechnology improvements, different metal nanomaterials have been also developed to enhance the antitumor efficacy of radiotherapy. In particular, silver nanoparticles (AgNPs) showed excellent radiosensitizing properties that have been confirmed on glioma cells in vitro and in vivo [ 46 , 111 , 112 , 113 , 114 ]. Thus, in order to enhance the radiosensitivity of tumor cells, Zhao and co-authors [ 46 ] conjugated NPs with polyethylene glycol (PEG) and the AS1411 aptamer (AsNPs), and demonstrated that conjugated AsNPs led to a lower cytotoxicity and enhanced the AgNP endocytosis into C6 GBM cells.…”
Section: Aptamers Showing In Vivo Therapeutic Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the nanotechnology improvements, different metal nanomaterials have been also developed to enhance the antitumor efficacy of radiotherapy. In particular, silver nanoparticles (AgNPs) showed excellent radiosensitizing properties that have been confirmed on glioma cells in vitro and in vivo [ 46 , 111 , 112 , 113 , 114 ]. Thus, in order to enhance the radiosensitivity of tumor cells, Zhao and co-authors [ 46 ] conjugated NPs with polyethylene glycol (PEG) and the AS1411 aptamer (AsNPs), and demonstrated that conjugated AsNPs led to a lower cytotoxicity and enhanced the AgNP endocytosis into C6 GBM cells.…”
Section: Aptamers Showing In Vivo Therapeutic Effectsmentioning
confidence: 99%
“…In addition, only the PEG–AS1411 conjugated nanoparticles reached the spheroid core, suggesting an improved penetration ability. Since previous studies indicated the apoptosis induction as a potential mechanism of radiosensitization, the authors demonstrated that AsNPs carried out their radiosensitizing function triggering the apoptotic response [ 46 ]. For the in vivo radiosensitization experiments, AsNPs were conjugated with the Cy5 fluorophore and systematically administrated to nude mice bearing intracranial glioma.…”
Section: Aptamers Showing In Vivo Therapeutic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogously, the combination of silver nanoparticles with polyethylene glycol (PEG)-functionalized AS1411 aptamer improved the outcome of radiation therapy in preclinical glioma models. Significantly prolonged median survival times were shown in animals undergoing the combined aptamer radiotherapy protocol vs. aptamer treatment alone [76]. Apart from metal formulations, the anti-MUC1 aptamer was conjugated to the radiosensitizer 1,10 phenanthroline for in-vitro radiosensitization of breast cancer cells, although the actual radiosensitizing potential of this complex has not yet been fully proven [77].…”
Section: Aptamers With Metal (Nano-)formulationsmentioning
confidence: 99%